Avaliação da atividade hipoglicemiante do extrato de Myrcia bella em camundongos diabéticos por estreptozotocina - Vareda, Priscilla Maria Ponce [UNESP] (2013)
Diabetes mellitus (DM) is characterized as a metabolic disorder resulting in defects of action and/or insulin secretion, resulting in disturbances in the metabolism of proteins, carbohydrates and lipids which can cause serious consequences to diabetic patients, resulting in complications such as weight loss, increased blood lipid levels, increased incidence of atherosclerosis and peripheral artery diseases, vision and kidneys injury, and in severe cases, death. The incidence of diabetics worldwide is increasing alarming over the years, and recent research has shown that the number of diabetics in the population will tend to a significantly increasing in coming decades. This alarming increase in the incidence of diabetes is due to the current lifestyles including unhealthy habits, sedentary lifestyle and obesity. Current treatments for diabetes include the use of exogenous insulin, as well of oral hypoglycemic agents. However, patients report numerous side effects and discomfort caused by them. Based on this information, the search for new agents that can act to improve diabetes has become the focus of several studies. In this context, the study of medicinal plants that has hypoglycemic effects and that acts in improving the diabetic state coming arousing interest of researchers. Myrtaceae is a botanical family that has many representatives in the Brazilian flora, and thus generates much interest in research on their species. The genus Myrcia is still not well explored by the researchers, and there are a few studies about the hypoglycemic activity of species in that genus. Thus, the aim of this study was to evaluate the possible hypoglycemic activity of the crude extract of the leaves of Myrcia bella Cambess, a plant from the Brazilian cerrado, in streptozotocin-induced diabetic mice. Diabetic (STZ SAL and STZ EXT) and control mice (CTL SAL and CTL EXT) were treated during 21 days with saline and the crude extract of ...